PPARA intron 1 A/C polymorphism and elite athlete status - Eynon, N.; Alves, A. J.; Yamin, C.; Meckel, Y. (European Journal of Sport Science, 2011)
Peroxisome proliferator-activated receptor alpha (PPARa) is involved in lipid and carbohydrate metabolism. The aim of this study was to test for a possible association between the PPARA intron 1 A/C polymorphism (rs135539) and the attainment of elite athlete status. In total, 155 Israeli athletes (119 males, 36 females) and 240 healthy controls (170 males, 70 females) participated in the study. The group of athletes consisted of endurance athletes (n=74) and sprinters (n=81). Genotyping was performed using PCR-RFLP on DNA from leucocytes. Results showed that genotype distribution and allele frequencies were similar (P=0.65 for genotypes and P=0.48 for allele frequency) for the endurance athletes (allele frequency A/C 0.7/0.3), sprinters (allele frequency A/C 0.66/0.34), and controls (allele frequency A/C 0.71/0.29). Furthermore, no significant differences were observed between the sub-groups of elite endurance athletes (those who had represented Israel in world track-and-field championships or in the Olympic Games) and national-level endurance athletes (P=0.44 for genotypes and P=0.96 for allele frequency), or between elite and national-level sprinters (P=0.57 for genotypes and P=0.40 for allele frequency). In conclusion, we observed no differences in genotype distribution or allele frequencies across PPARA intron 1 A/C polymorphism between endurance athletes, sprinters, and controls. Further research is needed in other ethnic groups to verify these results.